Interreligious Communication Perspective of the Qur'an Surah Al-Hujurat Verse 13 - Adinda Adinda (Edumaspul: Jurnal Pendidikan, 2024)
This research discusses the concept of interreligious communication in the context of the Qur'an, focusing on Surah Al-Hujurat Verse 13. This Surah teaches the basic principles of human relations, which emphasize the importance of tolerance and respect for differences in race, culture, and belief. This research uses qualitative analysis and literature review methods to analyze the data and find conclusions. Tolerance means respecting, allowing, and freeing others to behave and act in a way that is consistent with their rights, as long as it does not harm or infringe upon the rights of others. The results show that Surah Al-Hujurat Verse 13 contains teachings that support values and principles relevant to the vision of society which prioritizes diversity, inclusiveness, morality, and collaboration in creating a harmonious and sustainable society. Religious moderation in the context of society can play an important role in maintaining social harmony and contributing to the creation of a more harmonious society.